Effects of Advanced Platelet Rich Fibrin (A-PRF+), Enamel Matrix Derivative (EMD) and Open Flap Debridement on clinical and wound healing parameters in molar furcation sites: A case series from a RCT study - Pitzurra, L.; Vasdravellis, D.; Rosema, N.A.M.; Bizzarro, S.; Loos, B.G. (Frontiers in Dental Medicine, 2023)
Aim: To study effects of advanced platelet rich Fibrin (A-PRF+) and enamel matrix derivative (EMD) compared to open flap debridement (OFD) alone in molar furcation sites grade II on clinical and wound healing parameters.A randomized controlled trial was designed. Eligible patients were randomly allocated in one of three treatment groups: A-PRF+, EMD or OFD. The patients and clinical examiners were blinded for the treatment received. A minimally invasive microsurgical approach was performed for the three modalities. Clinical measurements were scored at baseline and 6 months postoperatively. The clinical healing of each furcation was scored via Early Wound Healing Index on day 3, 1 week, 2 weeks and 6 weeks.Results: 17 patients (A-PRF+ n=6, EMD n=5, OFD n=6) completed the 6 months follow-up.The further completion of the trial had to be cancelled due to the COVID-19 pandemic. In three patients in the A-PRF+ group, the grade II of the treated furcation regressed to grade I; the corresponding number in the EMD and OFD groups were zero and one respectively. Further, 3, 1 and 4 patients in the PRF, EMD and OFD groups respectively, showed a gain of bone level ≥1 mm. The defects in the A-PRF+ group showed delayed early healing compared to EMD and OFD groups.The case series (RCT design) suggest a slight advantage for A-PRF+ over EMD and OFD, regarding the regressing of a furcation II to grade I, however this treatment showed delayed early wound healing compared to EMD or OFD.